Are Additional Tests Needed to Rule Out Axial Spondyloarthritis in Patients Ages 16–45 Years With Short‐Duration Chronic Back Pain and Maximally One Spondyloarthritis Feature?. Issue 11 (6th October 2016) - Bakker, P. A. C.; Ez‐Zaitouni, Z.; van Lunteren, M.; van den Berg, R.; De Hooge, M.; Fagerli, K. M.; Landewé, R.; van Oosterhout, M.; Ramonda, R.; Reijnierse, M.; van der Heijde, D.; van Gaalen, F. A.
Abstract : Objective: To investigate whether HLA–B27 testing and imaging of the sacroiliac joints are needed in patients with ≤1 spondyloarthritis (SpA) feature, referred to a secondary care setting, after medical history collection, clinical examination, and measurement of acute phase reactants. Methods: Baseline data from patients in the Spondyloarthritis Caught Early (SPACE) cohort visiting the rheumatology outpatient clinic of 5 centers across Europe (with back pain ≥3 months, ≤2 years, onset at ages <45 years) were used. All patients underwent a full diagnostic work‐up: magnetic resonance imaging (MRI) and radiographs of the sacroiliac joints, HLA–B27 testing, and assessment of all other SpA features. Patients were diagnosed according to the treating rheumatologist and classified according to the Assessment of SpondyloArthritis international Society (ASAS) axial SpA criteria. Results: Of the 354 patients, 133 (37.5%) showed 0 or 1 SpA feature after medical history collection, physical examination, and measurement of acute phase reactants (38 without SpA features, 95 with 1 SpA feature). Of the patients with ≤1 SpA feature, 18.4% (with 0 SpA features) and 17.9% (with 1 SpA feature) were diagnosed with axial SpA according to the rheumatologist after additional investigations (HLA–B27 testing and sacroiliac joint imaging). Additionally, 4 of 38 patients (10.5%) without SpA features fulfilled the ASAS axial SpA criteria (all according to the imaging arm only: 2 as MRI+/modified New York criteria (mNY)+, 1 as MRI+/mNY−, and 1 as MRI−/mNY+). Of the 95 patients with 1 SpA feature, 22 (23.2%) fulfilled the ASAS axial SpA criteria (all according to the imaging arm only: 3 as MRI+/mNY+, 15 as MRI+/mNY−, and 4 as MRI−/mNY+). Conclusion: In these patients in a secondary care setting with ≤1 SpA feature, axial SpA could not be ruled out without sacroiliac joint imaging and/or HLA–B27 testing.